THE EVALUATION OF ACCOUNTING INFORMATION SYSTEM FOR DPK IN DISTRIBUTING AND MONITORING THE STUDENT FUND TO STUDENT CLUB IN UNIVERSITY OF SURABAYA - Muhammad Nugraha Eka Wardana (CALYPTRA, 2018)
The purpose of this research is doing evaluation of implementation accounting information system for DPK (Direktorat Pengembangan Kemahasiswaan) in distributing and monitoring the Student Fund (Dana Kemahasiswaan) to Student Club (Unit Kegiatan Mahasiswa) in UBAYA. DPK is the division that take responsible to distribute the funds. When the student club want to held an event, one of their source funding is come from university fund called student funding. The researcher want to evaluate the system whether it can be improve in effective and efficient ways, and also give the recommendation for the problem occurred. This research use the qualitative method by gathering information toward observation, interview both to UKM and DPK, also by documentary analysis as the collection method. The process being reviewed is from proposal process until the accountability report (Laporan Pertanggung Jawaban) of event submitted to university.